Eye Gaze in Intelligent User Interfaces Gaze-based Analyses, Models and Applications - Nakano, Yukiko I.; Conati, Cristina; Bader, Thomas; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Remarkable progress in eye-tracking technologies opened the way to design novel attention-based intelligent user interfaces, and highlighted the importance of better understanding of eye-gaze in human-computer interaction and human-human communication. For instance, a user$1 (Bs focus of attention is useful in interpreting the user$1 (Bs intentions, their understanding of the conversation, and their attitude towards the conversation. In human face-to-face communication, eye gaze plays an important role in floor management, grounding, and engagement in conversation. Eye Gaze in Intelligent User Interfaces draws on ideas from a number of contributors working on how attentional information can be applied to novel intelligent interfaces. Part I focuses on analyzing human eye gaze behaviors to reveal characteristics of human communication and cognition; Part II addresses estimation and prediction of the cognitive state of the users using gaze information; and Part III presents proposals of novel gaze-aware interfaces which integrate eye-trackers as a system component. The contributions highlight a direction for the future of human-computer interaction, and discuss issues in human attentional behaviors and face-to-face communication which are essential in designing gaze aware interactive interfaces.s
Preface -- Introduction -- Part I: Gaze in Human Communication -- How Eye Gaze Feedback Changes Parent-child Joint Attention in Shared Storybook Reading: An Eye-tracking Intervention Study -- Shared Gaze in Situated Referential Grounding: An Empirical Study -- Automated Analysis of Mutual Gaze in Human Conversational Pairs -- Part II: Gaze-based Cognitive and Communicative Status Estimation -- REGARD: Remote Gaze-Aware Reference Detector -- Effectiveness of Gaze-based Engagement Estimation in Conversational Agents -- A Computational Approach for Prediction of Problem-solving Behavior using Support Vector Machines and Eye-tracking Data -- Part III: Gaze Awareness in HCI -- Gazing the Text for Fun and Profit -- Natural Gaze Behavior as Input Modality for Human-Computer Interaction -- Co-present or Not?: Embodiment, Situatedness and the Mona Lisa Gaze Effect -- Index.
Keywords: Computer science; Multimedia systems; Computer vision; Social sciences -- Data processing; Education; Computer Science; User Interfaces and Human Computer Interaction; Computer Appl. in Social and Behavioral Sciences; Computers and Education; Computer Imaging, Vision, Pattern Recognition and Graphics; Multimedia Information Systems